(untitled) (Conversatoria Linguistica, 2019)
Linguistics today, the first decade of XXI century, is a creative continuation of the earlier methodological paradigms, ie, historical linguistics, comparative linguistics, structuralistic linguistics, and the emergence of new paradigms in linguistics is open to other disciplines, like sociology, anthropology, psychology, etc. which gives, inter alia, cognitivism, on the one hand, and the other comunicativism.